HOMOLOGI STRUKTURAL ANTARA SALIHARA DENGAN RUMAH ASAP DALAM SAMAN (Structural Homology of Salihara and the Smokehouse in Saman) - Muhammad Qadhafi (Kantor Bahasa Provinsi Sulawesi Tenggara, 2022)
This study focuses on the problem of the relationship between the KUK/Salihara structure and the smokehouse structure in Ayu Utami's novel Saman. This study aims to find the relationship between the dominant position of KUK/Salihara and its structure and to describe the structural homology between KUK/Salihara and the Smokehouse in Saman. This study uses qualitative data collection methods. The researcher used Bourdieu's arena construction method and the Social Network Visualizer (SocNetV) application to visualize the structure. In addition, researchers also use SocNetV's “centrality analysis” feature to determine the centrality of an agent. The results of this study are: 1) KUK/Salihara occupies a dominant position in the modern Indonesian literary field because of the high level of cultural capital, social capital, and economic capital. The acquisition of these capitals is closely related to the role of KUK/Salihara as a mediator that connects the literary field with other cultural fields, making it easier for them to exchange capital and monopolize legitimacy; 2) structural homology between KUK/Salihara and Saman shows that: a) both carry the same doxa, namely